PENGUNGKAPAN DIRI MELALUI MEDIA SOSIAL DAN KOMUNIKASI INTERPERSONAL DITINJAU DARI JENIS KELAMIN PADA SISWA (SELF-DISCLOSURE THROUGH SOCIAL MEDIA AND INTERPERSONAL COMMUNICATION REVIEW OF GENDER OF STUDENTS) - Twi Lia Widiyawati; Dyah Astorini Wulandari (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This study aims to determine the relationship between self-disclosure through social media with interpersonal communication in terms of gender in adolescents. This research is a quantitative research. The research population was 150 students with a sample of 108 students. The data collection technique in this study used a simple random sampling technique. The data collection method used interpersonal communication scale (31 valid items, = 0.874 ) and self-disclosure through social media (23 valid items, = 0.911 ). The results of data analysis using Pearson's product moment and obtained a p significance value of 0.008 (p < 0.05). These results indicate that the hypothesis is accepted, namely that there is a relationship between self-disclosure through social media and interpersonal communication in MTS Al-Hidayah Purwokerto students. And the Pearson correlation value of -0.254 which produces a negative correlation. And it can be concluded that there is a significant but negative relationship where the higher the self-disclosure through social media, the lower the interpersonal communication, and conversely the lower the self-disclosure made through social media, the higher the interpersonal communication. Based on the results of the independent samples test, the significance of 0.319 (sig < 0.05) indicates that there is no significant difference between self-disclosure in boys and girls. as well as interpersonal communication with a significance of 0.109 (sig < 0.05) indicates that there is no significant difference in interpersonal communication between men and women.